2020
DOI: 10.1097/wnp.0000000000000488
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potentials of Localized Blood–Brain Barrier Disruption by Noninvasive Transcranial Focused Ultrasound: A Technical Review

Abstract: Summary: The demands for region-specific, noninvasive therapies for neurologic/psychiatric conditions are growing. The rise of transcranial focused ultrasound technology has witnessed temporary and reversible disruptions of the blood–brain barrier in the brain with exceptional control over the spatial precisions and depth, all in a noninvasive manner. Starting with small animal studies about a decade ago, the technique is now being explored in nonhuman primates and humans for the assessment of its ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 80 publications
0
15
0
Order By: Relevance
“…In our study, DCE-MRI following the tFUS session showed no evidence of BBB disruption. As pressure and the associated mechanical index (MI) are important indicators for achieving BBB disruption [ 6 ], we conjecture that the acoustic pressure level used in this study ( in situ pressure of ~135 kPa and MI of 0.27), which was under the threshold for creating stable cavitation of MBs, was not high enough to cause BBB disruption. This conjecture is consistent with a previous investigation involving sheep in which localized enhancement of BBB permeability occurred in regions subjected to acoustic pressure levels greater than 480 kPa (MI, 0.96) after intravenous injection of the same type of MBs [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our study, DCE-MRI following the tFUS session showed no evidence of BBB disruption. As pressure and the associated mechanical index (MI) are important indicators for achieving BBB disruption [ 6 ], we conjecture that the acoustic pressure level used in this study ( in situ pressure of ~135 kPa and MI of 0.27), which was under the threshold for creating stable cavitation of MBs, was not high enough to cause BBB disruption. This conjecture is consistent with a previous investigation involving sheep in which localized enhancement of BBB permeability occurred in regions subjected to acoustic pressure levels greater than 480 kPa (MI, 0.96) after intravenous injection of the same type of MBs [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is also in agreement with a study by Hynynen and colleagues [ 22 ], which reported that an in situ pressure of 200 kPa (MI of >0.4) was needed to induce BBB disruption when 0.05 mL/kg dose of MBs (Optison, GE Healthcare, Princeton, NJ, USA) was used in rabbits at a similar tFUS frequency (i.e., 260 kHz) and pulsing scheme (10 ms tone-burst duration, 1 Hz sonication for 20 s). As successful BBB disruption depends on many factors, such as the type of MBs, sonication parameters, and transducer configuration, and given that excessive disruption may cause deleterious effects such as microhemorrhage [ 6 ], cautionary countermeasures such as acoustic emission detection of undesirable inertial cavitation [ 23 ] are needed to promote the safety of the procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both stable and inertial cavitation together with microbubbles can help open the BBB. However, whereas stable cavitation disrupts the BBB via wobbled expansion and contraction of microbubbles, inertial cavitation is caused by the violent collapse of the microbubbles, which could lead to vascular damage [ 49 ]. The first study of ultrasound-induced BBB opening showed small lesions with severe parenchymal damage [ 50 ].…”
Section: Ultrasound Applications In Ischemic Strokementioning
confidence: 99%
“…Transcranial ultrasound such as opening blood-brain barrier (BBB) ( Cammalleri et al, 2020 ) for localized drug release and modulating neural activity ( Nicodemus et al, 2019 ; Legon et al, 2014 ; David et al, 2014 ) has been used for therapeutic treatments of various brain diseases. Many in vivo animal experiments and human clinical trials ( Supplementary file 1 ) proved the clinical potential of transcranial ultrasound stimulation.…”
Section: Introductionmentioning
confidence: 99%